Isolation, culture, and cryosectioning of primary porcine retinal pigment epithelium on transwell cell culture inserts - Erika M.S. Hood; Christine A. Curcio; Daniel Lipinski (STAR Protocols, 2022)
Summary: Primary culture and long-term maintenance of primary retinal pigment epithelium (RPE) is a useful model system for the study of ocular pathologies such as age-related macular degeneration. Here, we detail the steps for the isolation and long-term culture of primary porcine RPE. We also describe steps for cryoprotecting, cryosectioning, and interrogating with immunofluorescence and histochemistry RPE cells grown on transwell membranes. These techniques can be used in histological studies to detect sub-RPE deposits.For complete details on the use and execution of this protocol, please refer to Pilgrim et al., (2017). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.